Does the number or the composition of players matter on the mobile broadband markets? – Lessons from a benchmarking study of the large-screen mobile broadband prices in the European Union - Zoltan Papai; Peter Nagy; Bertalan Papp (International Telecommunications Society (ITS), 2016)
Cross-country price comparison is a useful, but often deceptive exercise. The paper addresses the underlying methodological challenges, offering a practicable solution, which is both sound enough and meaningful for the comparison of prices on different markets. The simple and methodologically more sophisticated comparisons in turn give valuable insights into how the structural and also other factors associated with the price-differences between national markets.
Keywords: 330